Investigation of a Leakage Reactance Brushless DC Motor for DC Air Conditioning Compressor - Khlifi, M. A.; Ben Slimene, M.; Alradedi, A.; Al Ahmadi, S. (Engineering, Technology & Applied Science Research, 2022)
Home appliances using Brushless DC (BLDC) motors, such as Air Conditioners (ACs) and ceiling and pedestal fans, are gaining attention these days due to their low power consumption and low maintenance cost. This paper estimates and analyzes the leakage reactance of conventional and flux-switching permanent magnet BLDC motors. The leakage magnetic field of a high-power BLDC motor will be one of the main sources of interference. The magnetic field characteristics of the leakage field of a BLDC motor must be analyzed in order to acquire correct geomagnetic data. We also show the rotor's leakage magnetic field while the BLDC motor is static, the stator and rotor's leakage magnetic fields when the BLDC motor is functioning, and the near-field characteristic of the BLDC motor's leakage magnetic field.